The Influence of Fluid Management on Outcomes in Preeclampsia: A Systematic Review and Meta-Analysis. Issue 1 (March 2019) - Pretorius, T.; van Rensburg, G.; Dyer, R.A.; Biccard, B.M.
Abstract : ( Int J Obstet Anesth . 2018;34:85–95) One of the leading causes of maternal mortality is complications due to hypertensive disorders of pregnancy. Many guidelines for severe preeclampsia advocate a restrictive approach to fluid management; however, data to support these recommendations are limited. This systematic review and meta-analysis was undertaken to update the evidence regarding the effect of fluid management in preeclampsia on patient outcomes.